2012
DOI: 10.1177/1756287212457114
|View full text |Cite
|
Sign up to set email alerts
|

Mirabegron: a review of recent data and its prospects in the management of overactive bladder

Abstract: Recent advances in the understanding of the physiopathology of OAB have driven a huge amount of basic and clinical research into novel pharmacological compounds. Among potential novel peripherally acting drugs, β3-adrenoceptor (AR) agonists appear very promising [Sacco et al. 2008]. Mirabegron (also known as YM178) is a novel, once-daily orally active, first-in-class, potent β 3-AR agonist [Takasu et al. 2007]. Regulatory applications for mirabegron are under review in several countries. In July 2011, mirabegr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
75
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 33 publications
(54 reference statements)
5
75
0
3
Order By: Relevance
“…A 12-month study comparing mirabegron and tolterodine ER 4 mg in OAB reported that dry mouth, which contributed to the improved cost-effectiveness of mirabegron in the current analysis, was more frequently observed with tolterodine ER 4 mg. 54,55 Anticholinergic side effects are also likely to affect medication persistence and adherence, which are reported to decrease one month after treatment initiation with antimuscarinics. 24,56 Medication persistence and adherence are also reported to be important drivers of cost-effectiveness 57 and early real-world evidence in Canada suggests that median treatment persistence is greater with mirabegron (299 days or 196 days) compared to different antimuscarinics (96-242 days or 70-100 days) in previously treated and treatment-naïve patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 12-month study comparing mirabegron and tolterodine ER 4 mg in OAB reported that dry mouth, which contributed to the improved cost-effectiveness of mirabegron in the current analysis, was more frequently observed with tolterodine ER 4 mg. 54,55 Anticholinergic side effects are also likely to affect medication persistence and adherence, which are reported to decrease one month after treatment initiation with antimuscarinics. 24,56 Medication persistence and adherence are also reported to be important drivers of cost-effectiveness 57 and early real-world evidence in Canada suggests that median treatment persistence is greater with mirabegron (299 days or 196 days) compared to different antimuscarinics (96-242 days or 70-100 days) in previously treated and treatment-naïve patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, mirabegron 50 mg significantly reduced the number of Grade 3 and 4 urgency episodes per day vs. placebo in SCORPIO and the mean change (-2.25) was similar to tolterodine ER 4 mg (-2.07). 29 Another assumption of the model was that OAB symptoms improve during the first three months of treatment and are stable thereafter; this is supported by data from the 12-month study comparing mirabegron and tolterodine ER 4 mg. 54,55 Another assumption was that patients who discontinued treatment would not switch to another drug. Although information on this aspect of patient management is limited, there are data indicating that the majority of patients discontinue drug therapy after their first treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While the potential for CYP450 interactions exists, the presence of multiple metabolic pathways reduces the likelihood of clinical significance of each. So far, large placebo-controlled studies have shown mirabegron to be very effective in reducing incontinence episodes, micturitions in 24 hours, and urgency episodes versus placebo and tolterodine [24]. In a most recent meta-analysis comparing mirabegron to other antimuscarinics, the results showed similar efficacy with incidence of dry mouth similar to placebo [26].…”
Section: New Treatment Optionsmentioning
confidence: 98%
“…Mirabegron is an agonist at the β3 adrenergic receptor in the detrusor muscle. β3 accounts for 95% of all β-adrenergic receptors in the bladder [24]. Binding at this receptor facilitates smooth muscle relaxation, thus reducing urge, frequency, and incontinence episodes without systemic anticholinergic side effects [25].…”
Section: New Treatment Optionsmentioning
confidence: 99%
“…In particular, Mirabegron is a β3-adrenoreceptor agonist currently approved to treat overactive bladder. Phase II studies and four large-scale phase III multinational randomized, controlled trials have supported the efficacy of mirabegron in the clinical trial of patients with overactive bladder during 12 weeks and also for 12 months [112]. Surprinsingly, Mirabegron has been assigned to raise resting metabolic rate and BAT thermogenesis [113].…”
mentioning
confidence: 99%